NATO's southern allies : internal and external challenges - Chipman, John (Atlantic Institute for International Affairs research volume., 1988)
This book takes a careful look at foreign and defence policy formulation and assesses the perspective of the NATO states whose primary security concerns lie in the southern area of the Alliance and the military threats they face.